Therapeutic Agency Inventory: Development and psychometric validation of a patient self-report. (8th October 2019) - Huber, Julia; Nikendei, Christoph; Ehrenthal, Johannes C.; Schauenburg, Henning; Mander, Johannes; Dinger, Ulrike
Abstract: Objectives: Therapeutic agency is defined as a patient's intentional influence over the process of psychotherapeutic change. However, there is a lack of conceptually sound self-report measures with adequate psychometric properties. The aim of this study was to develop and psychometrically evaluate the patient-rated Therapeutic Agency Inventory (TAI). Method: Based on the literature, we developed items related to therapeutic agency and investigated their psychometric properties in a naturalistic study with a sample of 334 psychotherapy participants. We assessed changes in TAI scores in a subsample of 58 patients over the course of inpatient psychotherapy and related TAI scores to therapeutic improvement. Results: The TAI consists of 15 items. We performed exploratory factor analyses, and the following three factors were extracted: In-session activity, therapy-related processing, and therapist-oriented passivity. Internal consistency was .84 for the total score and ranged between .73 and .80 for each of the factors. The TAI was significantly associated with other psychotherapy process factors, self-efficacy expectations, control beliefs, lower overall psychological distress, and lower depression scores. Changes in agency during psychotherapy predicted therapy outcome, even after controlling for baseline distress. Conclusions: The TAI is a reliable, valid, and change-sensitive self-report instrument that can be used to assess agency in psychotherapy.